2005
DOI: 10.1038/sj.tpj.6500314
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP2A6*1B genetic variant with the amount of smoking in French adults from the Stanislas cohort

Abstract: This study was designed in order to investigate the influence of the genetic polymorphism of CYP2A6 on the amount of smoking. In all, 463 French adults included in the Stanislas cohort were studied and underwent two examinations at 5 years distance (t 0 and t þ 5 years). Information on their smoking habits was collected. They were genotyped by RFLP for the CYP2A6*1A, CYP2A6*1B and CYP2A6*4 alleles. CYP2A6*1B and CYP2A6*4 allele frequencies were 32 and 4%, respectively. The subjects carrying the CYP2A6*1B allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 27 publications
4
29
1
1
Order By: Relevance
“…A gene conversion with CYP2A7 in the 3′-untranslated region (3′-UTR), described as CYP2A6*1B1 [34], is reported to be associated with either full [5,34] or even increased [9] enzyme activity. In Serbs, the frequencies of described CYP2A6 genetic variations, as well as of corresponding alleles and genotypes, were comparable with the results previously published for other Caucasians [27,35,36].…”
Section: Discussionsupporting
confidence: 78%
“…A gene conversion with CYP2A7 in the 3′-untranslated region (3′-UTR), described as CYP2A6*1B1 [34], is reported to be associated with either full [5,34] or even increased [9] enzyme activity. In Serbs, the frequencies of described CYP2A6 genetic variations, as well as of corresponding alleles and genotypes, were comparable with the results previously published for other Caucasians [27,35,36].…”
Section: Discussionsupporting
confidence: 78%
“…Other studies have failed to detect an association between genetically low CYP2A6 activity and the number of cigarettes smoked. Genetic variation in CYP2A6 did not correlate with the ability to quit smoking and there is no significant difference in the smoking status was observed according to the CYP2A6 genotype (Gambier et al, 2005;Tan et al, 2001). This discrepancy may be partly explained by the different frequencies of inactive allele.…”
Section: Resultsmentioning
confidence: 65%
“…As with many CYP genes, genotyping for the various alleles is difficult due to the risk of amplifying the homologous CYP2A7 pseudogene, and careful controls of the primary PCR products are necessary. The higher expression of the CYP2A6 enzyme among carriers of CYP2A6*1B apparently affects smoking behavior (Malaiyandi et al, 2005), and, for example, Gambier et al (2005) reported that subjects homozygous for CYP2A6*1B smoked more cigarettes per day as compared to subjects homozygous for CYP2A6*1A. In Japan, where the defective CYP2A6*4 allele is very common, carriers of this genotype have been shown to have less risk of tobacco-induced lung cancer .…”
Section: Cyp2a6mentioning
confidence: 99%
“…The CYP2A6 gene is highly polymorphic (Oscarson, 2001) and the variant genes of highest importance are CYP2A6*4, representing a gene deletion mainly present in Asian populations, CYP2A6*9, having a mutation in the TATA box which causes a decreased expression of the enzyme, and CYP2A6*1B, where a gene conversion event with CYP2A7 creates a 3 0 -UTR that stabilizes the corresponding mRNA (Wang et al, 2006), resulting in higher metabolism in vivo of, for example, nicotine (Nakajima et al, 2001;Gambier et al, 2005). The most important functionally altered allele, CYP2A6*4, has a 7-22% allele frequency in Asians, but only 0.5-1% in Caucasians (Oscarson et al, 1999).…”
Section: Cyp2a6mentioning
confidence: 99%